A study on fiber glass composite hovercraft hull with different wall thickness using generative structural analysis - Muhammad Aiman, Ahmad Fozi; Mohamed Tarmizi, Ahmad; Bakri, Bakar; Mohd Sabri, Hussin; Mohd Hafiezal, Mohd Radzi; Ahmad Fairuz, Mansor (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.it/